2011
DOI: 10.1021/jp111331q
|View full text |Cite
|
Sign up to set email alerts
|

Salt Has a Biphasic Effect on the Higher-Order Structure of a DNA−Protamine Complex

Abstract: We observed single DNA molecules by fluorescence microscopy to clarify the effect of protamine on their higher-order structure. With an increase in the protamine concentration, the conformation of DNA molecules changes from an elongated coil state to a compact state through an intermediate state. Furthermore, the long-axis length of DNA gradually decreases while maintaining a distribution profile with a single peak. Such behavior is markedly different from the conformational transition of DNA induced by small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…3(b) in a good agreement with earlier studies. 6,29,30 It is now clear that divalent cations, Mg(2+) and Ca(2+), as well as a monovalent cation, Na(+), inhibit spermidine-induced DNA compaction. The difference between divalent and monovalent cations is that the former condense DNA, whereas the latter have almost no apparent condensing effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b) in a good agreement with earlier studies. 6,29,30 It is now clear that divalent cations, Mg(2+) and Ca(2+), as well as a monovalent cation, Na(+), inhibit spermidine-induced DNA compaction. The difference between divalent and monovalent cations is that the former condense DNA, whereas the latter have almost no apparent condensing effect.…”
Section: Resultsmentioning
confidence: 99%
“…We have experimentally confirmed that the fluorescence dye, Gelgreen, at the adapted concentration exhibits negligible effect on the conformation of DNA molecules, referring to the past studies on the higher-order structure of DNA. [25][26][27][28][29][30][31] All observations were carried out at room temperature (24 • C).…”
Section: B Dna Conformation In Solution As Observed By Fluorescence mentioning
confidence: 99%
“…Although it is not doubted that the electrostatic interaction between protamine and DNA could produce compact structures, 6,12 detailed investigation of their local organization has not been reported so far. Among factors affecting protamine/DNA complexation process, DNA size is particularly relevant because it largely influences the DNA-polypeptide interaction.…”
mentioning
confidence: 99%
“…30 The extent of the compaction depends on the concentration of protamine and the ionic strength of the supporting buffer medium. 1,31 Inside regular, rectangular nanochannels with a cross section of 300 × 200 nm 2 , we have verified that T4-DNA can be compacted with 0.4 µM of protamine in 1×T buffer. With the addition of 10 mM NaCl to the 1×T buffer, the threshold for compaction decreased about tenfold to a protamine concentration of 0.03 µM.…”
Section: Resultsmentioning
confidence: 62%